Angina After Percutaneous Coronary Intervention: Patient and Procedural Predictors. (28th March 2023) - Collison, Damien; Copt, Samuel; Mizukami, Takuya; Collet, Carlos; McLaren, Ruth; Didagelos, Matthaios; Aetesam-ur-Rahman, Muhammad; McCartney, Peter; Ford, Thomas J.; Lindsay, Mitchell; Shaukat, Aadil; Rocchiccioli, Paul; et al.
Abstract : Background: Twenty percent to 40% of patients are affected by angina after percutaneous coronary intervention (PCI), which is associated with anxiety, depression, impaired physical function, and reduced quality of life. Understanding patient and procedural factors associated with post-PCI angina may inform alternative approaches to treatment. Methods: Two hundred thirty patients undergoing PCI completed the Seattle Angina Questionnaire (SAQ-7) and European quality of life–5 dimension–5 level (EQ-5D-5L) questionnaires at baseline and 3 months post-PCI. Patients received blinded intracoronary physiology assessments before and after stenting. A post hoc analysis was performed to compare clinical and procedural characteristics among patients with and without post-PCI angina (defined by follow-up SAQ-angina frequency score <100). Results: Eighty-eight of 230 patients (38.3%) reported angina 3 months post-PCI and had a higher incidence of active smoking, atrial fibrillation, and history of previous myocardial infarction or PCI. Compared with patients with no angina at follow-up, they had lower baseline SAQ summary scores (69.48±24.12 versus 50.20±22.59, P <0.001) and EQ-5D-5L health index scores (0.84±0.15 versus 0.69±0.22, P <0.001). Pre-PCI fractional flow reserve (FFR) was lower among patients who had no post-PCI angina (0.56±0.15 versus 0.62±0.13, P =0.003). Percentage change in FFR after PCI had a moderate correlation with angina frequency score at follow-up ( r =0.36, P <0.0001). Patients with post-PCI angina had less improvement in FFR (43.1±33.5% versus 67.0±50.7%, P <0.001). There were no between-group differences in post-PCI FFR, coronary flow reserve, or corrected index of microcirculatory resistance. Patients with post-PCI angina had lower SAQ-summary scores (64.01±22 versus 95.16±8.72, P ≤0.001) and EQ-5D-5L index scores (0.69±0.26 versus 0.91±0.17, P ≤0.001) at follow-up. Conclusions: Larger improvements in FFR following PCI were associated with less angina and better quality of life at follow-up. In patients with stable symptoms, intracoronary physiology assessment can inform expectations of angina relief and quality of life improvement after stenting and thereby help to determine the appropriateness of PCI. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03259815.